Program Yuk Nabung Saham terhadap Minat Investasi pada Kelompok UKM di Kota Medan Sumatera Utara - Liana, Vega; Silalahi, Purnama Ramadani; Ayuni, Putri; Syahputra, Rifandi (Ikatan Da'i Indonesia, 2023)
Let's invest in SME organizations in Medan, North Sumatra, and save stock for investment interest. The purpose of this study was to determine the influence of the